The Effect of Size and Crumb Rubber Composition as a Filler with Compatibilizer Pp-G-Ma in Polypropylene Blends and Sir-20 Compound on Mechanical and Thermal Properties - Frida, Erna (UI Scholars Hub, 2012)
Having been researched the development of thermoplastic elastomer material of polypropylene and natural rubber SIR- 20 compound with Crumb Rubber as the filler. Reinforced polypropylene with size 60 mesh with 1 mm, and the composition of the Crumb rubber (30, 40, and 50) wt%. Observed mechanical properties are tensile strength, fracture elongation, Young's modulus, tear strength and impact strength. Thermal properties are analyzed by DSC and DTA/TGA. It is acquired that for the size of 60 mesh crumb rubber tensile strength, fracture elongation, Young’s modulus, tear strength and impact strength are bigger than 1mm size. The addition of 60 mesh crumb rubber increases but it decreases by adding of 50 weight%. While for crumb rubber 1 mm tensile strength, fracture elongation, tear strength and impact strength decreas. Based on analysis of DSC that the addition of crumb rubber does not make a difference boiling point significantly between samples containing crumb rubber and polypropylene Analysis TGA/DTA to an increase in enthalpy and decomposition temperature with the addition of crumb rubber used and thermal stability.